Concurrent Increases in Leaf Temperature With Light Accelerate Photosynthetic Induction in Tropical Tree Seedlings - Kang, Hui-Xing; Zhu, Xin-Guang; Yamori, Wataru; Tang, Yan-Hong (Frontiers in Plant Science, 2020)
Leaf temperature changes with incident light, but it is unclear how the concurrent changes influence leaf photosynthesis. We examined the time courses of CO2 gas exchanges and chlorophyll fluorescence of seedling leaves in four tropical tree species in response to lightflecks under three different temperature conditions. The three conditions were two constant temperatures at 30 °C (T30) and 40 °C (T40), and a simulated gradually changing temperature from 30 to 40 °C (Tdyn). The time required to reach half of the full photosynthetic induction under T40 was similar to, or even larger than, those under T30. However, the induction of assimilation rate (A) and electron transport rate of photosystem II (ETR II) and Rubisco activation process were generally accelerated under Tdyn compared to those at either T30 or T40. The acceleration in photosynthetic induction under Tdyn was significantly greater in the shade-tolerant species than in the shade-intolerant species. A modified photosynthetic limitation analysis indicated that the acceleration was likely to be mainly due to ETR II at the early stage of photosynthetic induction. The study suggests that concurrent increases in leaf temperature with light may increase leaf carbon gain under highly fluctuating light in tropical tree seedlings, particularly in shade-tolerant species.